Cannabis use in older adults-comprehensive literature review - Mushtaq, Raheel; Haque, Muhammad Rehan Ul (International Journal of Research in Medical Sciences, 2024)
Interest in medical cannabis (MC) use is growing among older adults, driven by its potential for managing chronic conditions such as pain, Parkinson’s disease (PD), and sleep disturbances. However, despite increasing usage, evidence supporting its efficacy remains inconclusive, particularly regarding its effects on mental health, cognition, and quality of life. While MC may offer benefits, such as pain relief and anxiety management, the pharmacokinetic and pharmacodynamic changes associated with aging present unique challenges, including drug interactions and increased vulnerability to adverse effects. Additionally, older adults face an elevated risk of cannabis hazardous or harmful use, influenced by factors like chronic health conditions, cognitive decline, and polypharmacy. A literature search following SANRA guidelines and using PubMed and Google scholar from 1980 to 2024 was conducted, focusing on studies involving older adults and cannabis use. The consequences of cannabis use in this population may include cognitive impairment, cardiovascular issues, and increased risk of falls. This review of literature examines the trends in cannabis use among older adults, the potential benefits and risks, and the need for cautious management and screening to minimize harm. Educating healthcare providers and older adults on the risks of cannabis use and the importance of monitoring is essential. Further research is needed to explore the long-term effects and safety of cannabis in older adults to guide clinical practice.